Analysis of Factors Affecting the Use of Drop-Off Service Communities Among Universitas Brawijaya Students - Putri, Marcella Haspirani; Fadjar, Nurman Setiawan (Contemporary Studies in Economic, Finance and Banking, 2025)
This study examines the factors influencing the use of personal shopping communities among university students, particularly at Universitas Brawijaya. The research aims to analyze the impact of service quality, price, utility, and preference on the perceived utility of using these personal shopping communities. Employing a quantitative approach and logistic regression analysis, data were collected through questionnaires distributed to students utilizing personal shopping services. The findings reveal that service quality has a significant negative impact on utility, while utility itself exhibits a significant positive influence. Although price and preference are considered important, they do not show statistically significant effects. The study concludes that utility plays a crucial role in enhancing student satisfaction, whereas unmet quality expectations can reduce satisfaction levels. The implications of this research include the development of personal shopping business strategies that prioritize efficiency and student consumer needs, as well as theoretical contributions to the literature on consumer behavior in the digital era.